LabSchoolsEurope Participatory Research for Democratic Education - Kurz, Benedict; Zenke, Christian Timo (Impuls Laborschule, 2023)
Across Europe, laboratory schools find new ways to tackle the educational issues of our time. Their work is guided by educational experimentation and the aim to strengthen the bond between educational practice and research. In this book, lab schools from Bielefeld, Brno, Cambridge, Paris, and Vienna provide unique insights into how they bring John Dewey's framework for a lab school to life. This book is the result of the Erasmus+ project "LabSchoolsEurope: Participatory Research for Democratic Education". It is a testament to the potential of collaborating across borders.